(untitled) (Research, Society and Development, 2020)
Objective: This study aimed to investigate in the literature the effects of vitamin A supplementation or not in patients with cystic fibrosis (CF). Methodology: This is an integrative review carried out by searching for original articles, published in English, Portuguese and Spanish, indexed in the Scielo and Pubmed databases. Results: Of the 8 studies included in the review, 25% (n=2) identified an association between elevated serum retinol levels and improvement of the fibrocystic condition, and 50% (n=4) found positive effects on lung function and clinical conditions, from vitamin A supplementation. In contrast, 25% (n=2) did not observe any correlation between vitamin A use, although they identified an improvement in their status resulting from the intervention. Conclusion: Most studies have shown that the supplemented or not use of vitamin A proved to be potentially beneficial for the clinical and nutritional profile, as well as for the survival of patients with cystic fibrosis. However, there is a need for more research, especially in humans, that address the theme.